2015
DOI: 10.1371/journal.pone.0118681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Different Forms of Telemedicine for Individuals with Heart Failure (HF): A Systematic Review and Network Meta-Analysis

Abstract: BackgroundPrevious studies on telemedicine have either focused on its role in the management of chronic diseases in general or examined its effectiveness in comparison to standard post-discharge care. Little has been done to determine the comparative impact of different telemedicine options for a specific population such as individuals with heart failure (HF).Methods and FindingsSystematic reviews (SR) of randomized controlled trials (RCTs) that examined telephone support, telemonitoring, video monitoring or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(165 citation statements)
references
References 51 publications
5
156
1
3
Order By: Relevance
“…In a recent network meta-analysis of 30 RCTs by Kotb et al ,13 teletransmission was found to reduce the odds of mortality as well as the HF-related hospitalizations compared with the standard care. In addition, structured telephone support reduced the odds of HF-related mortality and hospitalizations, while ECG monitoring reduced the odds of HF-related hospitalizations 13.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent network meta-analysis of 30 RCTs by Kotb et al ,13 teletransmission was found to reduce the odds of mortality as well as the HF-related hospitalizations compared with the standard care. In addition, structured telephone support reduced the odds of HF-related mortality and hospitalizations, while ECG monitoring reduced the odds of HF-related hospitalizations 13.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent report, only 15% of family practitioners used telehealth to provide health care. 31 One adaptation of multidisciplinary disease management has been to use telephone calls. This strategy may e27…”
Section: Current Effective Telehealth Interventions In Cvdmentioning
confidence: 99%
“…Prior research in the area of TM has focused on the impacts of this patient management approach, mostly in relation to symptoms, mortality, and the utilization of services [17,18,23]. Yet, limited evidence exists on the actual effects of TM on patients' behaviors, especially patient empowerment and selfcare, with the exception of general discussion on patients' acceptability and attitude towards the technology.…”
Section: Literature Reviewmentioning
confidence: 99%